Berebut Wacana: Hilangnya Etika Komunikasi di Ruang Publik Dunia Maya - Saiful Mustofa (Jurnal Studi Agama dan Masyarakat, 2019)
The background of this study concern to phenomenon a communication ethics no longer exist in the social media public sphere. Social media, as one of the products of the digital revolution being a free stage to spread anxiety; ethnic, racial, and religious sentiments (SARA) to the legitimacy of the authority of truth. By using critical hermeneutic approach of Jürgen Habermas, this paper attempts to examine the phenomenon of discourse struggle which is dominated by hate speech in religion and hoax on social media for the period 2017-2018 which on average loses communication ethics. The struggle for discourse in social media public sphere shows the existence of strong political penetration by utilizing religious symbols as “weapons” so that the consensus on mutual understanding does not occur.